Family law : a very short introduction - Herring, Jonathan (Very short introductions.)
"What is a family? What makes someone a parent? What rights should children have? [This book] gives the reader insight not only into what the law is, but why it is the way it is. It examines how laws have had to respond to social changes in family life, from rapidly rising divorce rates to surrogate mothers, and gives insight into family courts, which are required to deal with the chaos of family life and often struggle to keep up-to-date with social and scientific changes. It also looks to the future: what will families look like in the years ahead? What new dilemmas will the courts face?" --Provided by publisher.